Synthesis and Applications of Glyconanoparticles - Liu, Baoyong; Lu, Xiaowei; Ruan, Hong; Cui, Jiwei; Li, Hongguang (Current Organic Chemistry, 2016)
Glyconanoparticles are the subject of numerous literatures and are emerging for applications in biomedicine, glycoscience, and material science due to their unique properties. They are hybrid materials each of which contains a nanoparticle core surrounded by a carbohydrate shell. The core can be metallic, magnetic, and/or photoluminescent, while the shell may be composed of mono-, di-, oligo- and/or poly-saccharides. Sugars are attached to the surface of the nanoparticles through covalent or non-covalent interaction. Here, we give a brief summary of the synthetic methodologies adopted in the preparation of different types of glyconanoparticles, which can be utilized in various applications including catalysis, drug delivery, vaccine, imaging and study of carbohydrate-lectin interactions.
Keywords: carbohydrate-lectin interactions